Examining the Sustainable Use of Organic Solvents for the Manufacture of Pharmaceutical Products - Choudhary, Varsha S (Digital Repository of Theses, 2025)
This study investigates the sustainable usage of organic solvents in pharmaceutical manufacturing, addressing their environmental and health impacts. The research focuses on three dimensions: the awareness of solvent-related negative impacts among pharmaceutical personnel and students, the practical applicability of regulatory norms governing solvent usage, and the feasibility of avoiding these solvents in manufacturing processes. Data was collected through a survey of 323 participants, encompassing industry professionals and students. The results reveal that while awareness of solvent impacts is moderate among students, professionals exhibit a deeper understanding, attributed to their direct involvement in manufacturing processes. Despite the existence of robust regulatory guidelines, challenges in their practical implementation persist due to resource constraints, varying enforcement standards, and industry resistance to change. The study also discusses alternative technologies, such as solvent-free methods and green chemistry principles, which demonstrate promise in reducing or eliminating organic solvent use without compromising product quality. However, widespread adoption requires substantial investment and industry collaboration. This research concludes that bridging awareness gaps, particularly among future professionals, is critical to fostering sustainable practices. It calls for targeted educational initiatives, enhanced policy enforcement, and incentives for adopting greener technologies. By addressing these gaps, the pharmaceutical industry can significantly reduce its reliance on organic solvents, contributing to global sustainability efforts.